Motivational Interviewing: moving from why to how with autonomy support - Resnicow Ken; McMaster Fiona (BMC, 2012)
Abstract Motivational Interviewing (MI), a counseling style initially used to treat addictions, increasingly has been used in health care and public health settings. This manuscript provides an overview of MI, including its theoretical origins and core clinical strategies. We also address similarities and differences with Self-Determination Theory. MI has been defined as person-centered method of guiding to elicit and strengthen personal motivation for change. Core clinical strategies include, e.g., reflective listening and eliciting change talk. MI encourages individuals to work through their ambivalence about behavior change and to explore discrepancy between their current behavior and broader life goals and values. A key challenge for MI practitioners is deciding when and how to transition from building motivation to the goal setting and planning phases of counseling. To address this, we present a new three-phase model that provides a framework for moving from WHY to HOW; from building motivation to more action oriented counseling, within a patient centered framework.